Pembuatan Sistem Informasi Pendataan Block Grant Dan Pengiriman Arsip Via Email Berbasis Database - ., Setiyono; Purnama, Bambang Eka; Wardati, Indah Uly (Speed - Indonesian Journal on Computer Science, 2014)
ABSTRACT: Information Systems is one right way to progress in school infrastructure kususnya SMP PGRI Sudimoro, Information Systems are also able to produce something that becomes more interesting and alive. One of them is the application of Information Systems in the SMP PGRI Sudimoro Block Grant for data collection. Junior High School PGRI Sudimoro is standing first in Kec.Sudimoro located in Ds.Sukorejo Kec.Sudimoro, since the establishment of the school has not been made that can manage Information System Block Grant data collection and delivery via email archives so well with the The school system is able to assist Parties School / foundations and SMP PGRI Sudimoro Administration in order to get maximum results. The methodology used is to study literature, Observation, Interviews, Analysis, Design, Shooting, Testing and Implementation.Results are expected in the manufacture of System Information Block Grant Data Collection and Delivery Records Via Email-based database can support the schools progress in particular in infrastructure, SMP PGRI Sudimoro purposes in order to produce an accurate output, maximum and timely. Keywords: Data Block Grant Collection and Delivery Records Information System ABSTRAKSI: Sistem Informasi adalah salah satu cara yang tepat untuk kemajuan sarana dan prasarana di sekolah kususnya SMP PGRI Sudimoro, Sistem Informasi juga mampu menghasilkan sesuatu hal menjadi lebih menarik dan hidup. Salah satunya penerapan Sistem Informasi di SMP PGRI Sudimoro yaitu untuk pendataan Block Grant.  Sekolah Menengah Pertama PGRI Sudimoro adalah Sekolah Menengah yang berdiri pertama di Kec.Sudimoro yang terletak di Ds.Sukorejo Kec.Sudimoro, sejak berdirinya sekolah tersebut belum pernah dibuatkan Sistem Informasi yang dapat mengelola pendataan Block Grant dan pengiriman arsip via email dengan baik sehingga  dengan adanya sistem ini sekolah mampu membantu  Pihak Sekolah/yayasan dan Tata Usaha SMP PGRI Sudimoro supaya  bisa  mendapatkan hasil yang maksimal. Kesimpulan dalam pembuatan Sistem Informasi Pendataan Block Grant dan Pengiriman Arsip Via Email berbasis database ini dapat menunjang kemajuan sekolah khususnya dalam sarana dan prasarana, tujuan SMP PGRI Sudimoro supaya dapat menghasilkan output yang akurat,maksimal dan tepat waktu. Kata Kunci : Sistem Informasi Pendataan Block Grant, Arsip, Berbasis Database